Malignant transformation of ovarian mature teratoma: 04 cases report, review of the literature - Jamor, Jihad; Conte, Alpha Boubacar; Fdili Alaoui, Fatima Zohra; Jayi, Sofia; Chaara, Hikmat; Melhouf, Moulay Abdelilah (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Mature ovarian teratomas or dermoid cysts are the most common ovarian germinal tumors and account for 20 to 25% of ovarian organ tumors. The malignant transformation of a mature teratoma is a rare event (1 to 3%), mainly found in the post-menopausal period. This is carcinomatous degeneration (80% of cases) or sarcomatous differentiated tissues of the dermoid cyst. The diagnosis of certainty is established by anatomopathological study of the surgical piece. Treatment of carcinoma teratomas is surgical and same to ovarian malignant epithelial tumors. We report four cases we managed in our health care center with a review of the literature.